MAT GLASS – THIN LAYER CHROMATOGRAPHY. APPLICATION OF INVASION MODEL - Mihaela VLASSA (Studia Universitatis Babes-Bolyai Chemia, 2023)
This study presents the theoretical and practical aspects of the new technique, namely Mat Glass - Thin Layer Chromatography (MG-TLC) and application of invasion model. Our research is focused on the development and clarification of the phenomena that occur in thin layer separation technique: process flow, spreading on mat glass surface, impregnation of porous layers and the improvement of the quality of thin layer chromatographic separations by overlapping some mat glass plates, over the chromatographic plates. The experiments have confirmed the possibility that the movement of the invasive type displacement, which occurs on rough surface will influence favorably the chromatographic separation processes. Good results have been obtained in separation of the lipophilic dyes and the hydrophilic dyes by small adjustments, e.g., height of the free zone of porous layer h, or the roughness of glass plates. The results obtained demonstrate that this method can be successfully used in thin layer chromatography technique being easy to apply and inexpensive compared with other methods derived from chromatography.